The Advancing Science by Enhancing Learning in the Laboratory (ASELL) project: the next chapter - Pyke, S.; Yeung, A.; Kable, S.; Sharma, M.; Barrie, S.; Buntine, Mark; Burke Da Silva, K.; Lim, K. (University of Sydney, 2011)
Most researchers agree that the laboratory experience ranks as a significant factor that influences students’ attitudes to their science courses. Consequently, good laboratory programs should play a major role in influencing student learning and performance. The laboratory program can be pivotal in defining a student's experience in the sciences, and if done poorly, can be a major contributing factor in causing disengagement from the subject area. The challenge remains to provide students with laboratory activities that are relevant, engaging and offer effective learning opportunities. The Advancing Science by Enhancing Learning in the Laboratory (ASELL) project has developed over the last 10 years with the aim of improving the quality of learning in undergraduate laboratories, providing a validated means of evaluating the laboratory experience of students and effective professional development for academic staff. After successful development in chemistry and trials using the developed principles in physics and biology, the project has now expanded to include those disciplines. This paper will discuss the activities of ASELL and provide a report about the first ASELL science workshop held at the University of Adelaide in April 2010.